Ellueššar, lalakueššar, suppaleššar: Collective animal nouns in -eššar in Hittite - Fagiolo, Virna (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2025)
This paper details an analysis of the derivational process in Hittite of collective nouns for animals characterized by the suffix -eššar, which is one of the Hittite heteroclitic suffixes in -r/-n- together with -(ā)tar and -war (-mar). As well as deriving action and abstract nouns from verbs and adjectives, this suffix seems to originate also some collectives from nouns. In particular, the three collective formations lalakueššar ‘colony of ants, anthill’ < lalakueša- ‘ant’, šuppaleššar ‘livestock, animal fence’ < šuppal(a)- ‘animal’ and the uncertain ellueššar < illu-, usually presented in relationship with the etymology of Hitt. illuyanka-, were taken here into consideration. The purpose of the analysis is firstly to investigate how these collective formations in -eššar fit the framework of collective nouns offered by the other Indo-European languages, and secondly, to examine the relationship between collective and place nouns using a comparative approach, since these collective formations in -eššar seem to develop a locative meaning.